If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 3x = 360 Reorder the terms: 3x + y = 360 Solving 3x + y = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + y + -1y = 360 + -1y Combine like terms: y + -1y = 0 3x + 0 = 360 + -1y 3x = 360 + -1y Divide each side by '3'. x = 120 + -0.3333333333y Simplifying x = 120 + -0.3333333333y
| (-6hi^3j^4)(6h^2i^0j^3)=0 | | x^4-7x^3-19x^2+163x-210=0 | | (18-x)(15+x)=266+3x-x^2 | | 0.025=w(1-0.59w) | | 8w=4880 | | 45x=89 | | 7x-2=X+2 | | 2(x-1)=4x-6 | | 0.592=4.25*d+6.8*d^2 | | 592=4.25*d+6.8*d^2 | | 4-12x+12h-9xh+9x^2+9h^2-2+3x= | | 2mx=18mn | | y=4.5x-2.5 | | 100x+10y=36z | | 2u+4u=54 | | 2ef+3ef-ef= | | x=x^2+11x+30 | | x^2+11x+30=15 | | 2x+7-69=0 | | 2y+x=41 | | 7*600000= | | 2x+4=6(x+4) | | 2x+1y=34 | | 8x^2-29x-1890=0 | | log(7)x+log(7)x+6=1 | | 1-6a=3a+8 | | 16+2y=1-y | | 0.25(4p-3)=0.05(10p-9) | | log(7)x+log(7)(x+6)=1 | | 5x-12y-11=0 | | x^2+10x=-30 | | 3a*6=12 |